PROSES PRODUKSI ROTAN DI PT.HOMEWARE INTERNATIONAL INDONESIA KABUPATEN CIREBON JAWA BARAT - Amin Hidayat; Whydiantoro (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Cirebon Regency is one of the cities in West Java that produces woven rattan furniture which is also capable of exporting abroad. There are not a few companies that exist in Cirebon district, there are several products such as chairs, tables, flower pots and so on. With the establishment of a rattan company in Cirebon Regency, it has opened up job vacancies for the people of Cirebon, and there are not even a few rattan woven workers who come from outside the city of Cirebon, such as from Majalengka, Kuningan, Indramayu Regencies and other cities around Cirebon Regency. But apart from that, more and more rattan companies in Cirebon have been established, resulting in less and less land in the rattan industrial area in Cirebon, land prices are increasingly expensive so that it can disrupt the production process that occurs in companies because market demand is increasing and booming and finally rattan companies in Cirebon district also have difficulties in developing their companies. Responding to the problems found, the company entered into work contract agreements with suppliers with the aim that the company does not need to prepare large areas of land to accommodate workers when they want to carry out the production process and prepare land for storage of rattan raw materials in the hope that they can export abroad but instead are able to produce more. many woven products produced by workers from suppliers. The company only needs to prepare the land for receiving semi-finished woven from suppliers, prepare a quality control team, as well as other processes such as finishing, packing and shipping to consumers. The existence of work contract agreements with suppliers makes the rattan production process very long, starting from giving SPK, purchasing raw materials, soaking raw materials, weaving processes, field quality control processes, shipping from suppliers to companies, the process of receiving goods from suppliers at the company, washing processes , the painting process, the final quality control process, the packing process, checking the temperature and humidity, up to the delivery process. The company hopes that by having a work contract agreement with suppliers it can fulfill market demand.